Catch composition, length frequency and biomass of commercial carps in Zayandehrud dam, Isfahan Province, Iran - MOHAMMAD REZA ABBASI; SEYED YOUSEF PAIGHAMBARI; MOJTABA POULADI; RASOUL GHORBANI (Society for Indonesian Biodiversity, 2017)
Abbasi MR, Paighambari SY, Pouladi M, Ghorbani R. 2017. Catch composition, length frequency and biomass of commercial carps in Zayandehrud dam, Isfahan Province, Iran. Biodiversitas 18: 939-944. The reservoir of Zayandehrud with an area of 4800 hectares due to its economic role is one of the important lakes in Isfahan Province. This study was performed from September 2015 to March 2016, to evaluate catch composition, length frequency and biomass of carps for sustainable utilization of fish resources. Sampling operations were performed using gill nets with mesh sizes including 40, 50, 60, 70, 80, 90, 120, and 150 mm (stretched) with a length of 1 to 3 km seasonally. A total of 617 fish with a total weight of 1109.7 kg were caught. The important species which were caught by fishing operations were including common carp (Cyprinus carpio), silver carp (Hypophthalmichthys molitrix), bighead carp (Hypophthalmichthys nobilis), grass carp (Ctenopharyngodon idella) and mesopotamian barb (Capoeta damascina), respectively. Due to natural reproduction season (spring, in July), the fishing season usually starts from August to the end of winter. Common carp with 292 pieces (47.32%), silver carp with 87 pieces (14%) and mesopotamian barb with 221 pieces (35.81%) had the most abundance; whereas crucian carp with 4 pieces (0.64%) and grass carp with 1 piece (0.16%) showed the lowest abundance. Also as the main species of study, highest length ranges of caught common carps were in the range of 38-45 cm and 46-50 cm in autumn and winter, whereas highest length ranges of caught silver carps were in the range of 56-86 cm and 48-54 cm in autumn and winter. Length - weight relationships of carp showed an isometric growth model that indicates homogeneous growth in fish.